Pengaruh Likuiditas dan Profitabilitas terhadap Keputusan Investasi pada Bank Umum Syariah yang Terdaftar di Bursa Efek Indonesia Periode 2021–2025 - Andi Muhammad Hanif; Muhammad Ichwan Musa; Andi Mustika Amin; Anwar Anwar; Annisa Paramaswary Aslam (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The rapid development of Islamic banking in Indonesia faces significant challenges in maintaining liquidity and profitability amidst dynamic capital market conditions. The urgency of this study arises from the need to examine whether traditional financial ratios, such as the Financing to Deposit Ratio (FDR) and Return on Equity (ROE), play a decisive role in influencing investment decisions, which are proxied by the Price to Earning Ratio (PER). The main objective of this research is to empirically test the effect of liquidity and profitability, both partially and simultaneously, on investment decisions in Islamic commercial banks listed on the Indonesia Stock Exchange during the 2021–2025 period. This study adopts an associative design with a quantitative approach, utilizing secondary data from financial reports obtained from the IDX, and analyzed using multiple linear regression on 68 observation samples. The findings reveal that neither liquidity nor profitability significantly influence investment decisions, either partially or simultaneously. These results suggest that investors in the Islamic banking sector tend to prioritize non-financial factors such as sharia compliance, governance, macroeconomic conditions, and ESG trends, rather than conventional financial indicators. In conclusion, this research extends the understanding of the limitations of Signaling Theory in the sharia context and recommends the development of a more holistic investment evaluation model. Future studies are encouraged to incorporate non-financial variables for a more comprehensive analysis.